Risk perception and management in development philanthropy. (18th November 2016) - Sargeant, Adrian; Shang, Jen
Abstract : For the research on which this article is based, twenty philanthropists, who devoted personal wealth in excess of $5 million to create social innovation in order to care for their beneficiaries, were studied in Decoding the Discipline (DtD) interviews. In this article, we contribute to the substantive psychology and management theories on risk in the domain of international development philanthropy by delineating the process by which the philanthropists overcame five major barriers in managing this high risk: (a) defining risks, (b) evaluating their severity, (c) how to decide when to shift mindset, (d) coping with negative emotions and (e) optimising the value that their life experience offers their philanthropy.